1994
DOI: 10.1159/000247083
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma Complicating Lichen planus: A Clinico-Pathological Study of Three Cases

Abstract: Squamous cell carcinoma complicating lichen planus is described in 3 patients. In 2, the cancers developed on the lower leg in chronic and hypertrophic lichen planus. In the other case, the cancer complicated lichen planus of the lip mucosa in a smoker. In the two cutaneous cases, the tumour and the adjacent skin showed features of lichen planus, including hypergranulosis, cytoid bodies and a lichenoid infiltrate. The association, though rare with cutaneous lichen planus when it tends to affect chronic hypertr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 7 publications
0
16
1
1
Order By: Relevance
“…In 2 of our patients, infiltrating cords of atypical keratinocytes were present in the deep dermis and were masked by overlying lichenoid infundibulocystic follicular hyperplasia. Although squamous cell carcinoma may develop in the setting of classic hypertrophic lichen planus, this usually emerges in the background of long-standing lichen planus, 12,13 in contrast to the short history and early lichenoid reactions seen in our patients.…”
Section: Commentcontrasting
confidence: 57%
“…In 2 of our patients, infiltrating cords of atypical keratinocytes were present in the deep dermis and were masked by overlying lichenoid infundibulocystic follicular hyperplasia. Although squamous cell carcinoma may develop in the setting of classic hypertrophic lichen planus, this usually emerges in the background of long-standing lichen planus, 12,13 in contrast to the short history and early lichenoid reactions seen in our patients.…”
Section: Commentcontrasting
confidence: 57%
“…Hypertrophic lichen planus is a subacute chronic variant of lichen planus characterized by hypertrophic or warty lesions most often found on the pretibial area of the lower limbs 1–3 . In the literature, 41 cases of lichen planus, mainly of hypertrophic or verrucous type, with consecutive carcinoma have been described 4–8 . X‐ray and arsenic treatment of lichen ruber often precedes malignant transformation by many years 5 .…”
Section: Discussionmentioning
confidence: 99%
“…gations that found that OSCC developed in lesions previously diagnosed as OLP (11)(12)(13)(14)(15). OSCC develops in 0.5% to 2.5% of OLP according to reports (16,17).…”
mentioning
confidence: 99%